Posted by **Katie** on Thursday, April 23, 2009 at 6:31pm.

the original problem was:

Solve: sin(3x)-sin(x)=cos(2x)

so far i've gooten to:

sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x)

Where would I go from here?

## Answer This Question

## Related Questions

- tigonometry - expres the following as sums and differences of sines or cosines ...
- Math - the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've ...
- TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...
- algebra - Can someone please help me do this problem? That would be great! ...
- Precal - I do not understand how to do this problem ((sin^3 A + cos^3 A)/(sin A...
- Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...
- Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...
- trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...
- Trigonometry - Solve the equation for solutions in the interval 0<=theta<...
- calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...

More Related Questions